Inhibitory Effect of Bombay Onion (Allium cepa L.) Extracts on Mitotic Chromosomes - Edy Suwarso; Dewi Nur Anggraeni (Indonesian Society for Cancer Chemoprevention, 2016)
Cancer is one of the world health problems. Free radical could damage cells and lead to cancer. Antioxidant compound could be found in some vegetable such as phenols and flavonoids. Flavonoids and phenol significantly decrease micronucleus formation on mitotic chromosomes. This present study aim to explore the inhibitory effect of Bombay onion extracts (BOE) on mitotic chromosomes induced by cyclophosphamide. Twenty-five mice (body weight 20–35 g) were divided into 5 groups, with 5 mice in each group. Normal control group (NCG) were given CMC 5 mg/mice/7 days. Mutagen control group (MCG) that is previously given as NCG, 4 hours later were given cyclophosphamide at a dose of 50.0 mg/kg bw intraperitoneally. Three treatment groups, group 1 (TG-1), TG-2, and TG-3, were given BOE with doses of 100; 200; and 400 mg/kg bw for 7 days, respectively. After 7 days, all three groups were treated similarly with MCG. Thirty hours later, all groups were put to death and femur bone marrows were analyzed to count the number of micronucleus. The results showed that the number of micronucleus in every 200 polychromatic erythrocyte cells at mitotic chromosomes for NCG is 29.8 ± 2.387, MCG with a value of 120.8 ± 5,718, TG-1 showed 94.8 ± 7.049, TG-2 is 68.8 ± 3.421, and TG-3 which is 30.8 ± 0.837. TG-3 showed a similar result with NCG (p> 0.05).Keywords : mitotic chromosomes, Bombay Onion Extracts, femur bone marrow, micronucleus